Pengaruh Total Quality Management (Tgm, Gaya Kepemimpinan,. Kedisiplinan Kerja dan Fungsi Monitoring) Terhadap Kinerja Karyawan - Heriyanto Heriyanto (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2018)
Influence Total of Quality Management (TQM), Style Leadership, JobDiscipline and Function of Mentoring to Performance Employees of PT.Kemakmurn Berkah Timber Samarinda.To be able improved Performance Employees in a company ororganization, hence required by factors able to improve Performance itself.As for the factors is Totalizeing Quality Management, Style Leadership, JobDiscipline and Function of Mentoring.This Formula research internal issue is" What is there Total influenceof Quality Management, Style Leadership, Job Discipline and Function ofMentoring to Performance Employees.This Research aim to know Total influence of Quality Management,Style Leadership, Job Discipline and Function of Mentoring to PerformanceEmployees.Method Research by using quesioner with scale of likert. Researchpopulation is entired all employees of PT. Kemakmuran Berkah Timber andof sampel research counted 45 employees people with technique intake ofsampel that is totalizeing sampling.Analyzer the used multiple regression which where beforehand haveto test and validity of reliabilitas and also test classic assumption.Pursuant to result of solution and research hence Totalizeing QualityManagement and Job Discipline have an effect on positive and significant toPerformance Employees, so that Ho refused and Style Leadership not havean effect on positive and not significant, so that Ho accepted. While Functionof Mentoring have an effect on positive but not significant to PerformanceEmployees, so that Ho accepted.From result of this research expected can be used as by input tomanagement side upon which consideration in order to make-up ofemployees performance.